Prison Rehabilitation Programs: Efficiency and Targeting - William Arbour; Guy Lacroix; Steeve Marchand (Institute of Labor Economics (IZA), 2021)
Increasing evidence suggests that incarceration, under certain circumstances, can improve inmates' social reintegration upon release. Yet, the mechanisms through which incarceration can lead to successful rehabilitation remain largely unknown. This paper finds that participation in social rehabilitation programs while incarcerated can significantly reduce recidivism. This result is entirely driven by inmates whose risk and needs were evaluated by a widely used assessment tool identifying their criminogenic needs. For this group, we estimate that participation in these programs reduces recidivism by about 9 percentage points within three years following release. Our results suggest targeting criminogenic needs is crucial for successful rehabilitation. We also find considerable heterogeneous program treatment effects: inmates with a high overall risk score, or who exhibit procriminal attitudes, benefit little if at all from program participation. We investigate the stability of the treatment effect coefficients and conclude they unlikely suffer from an omitted variable bias.
Keywords: K42; 330; incarceration; recidivism; rehabilitation programs; risk assessment